Treatment adherence and virological response rates in hepatitis C virus infected persons treated with sofosbuvir‐based regimens: results from ERCHIVES. (24th March 2016) - Butt, Adeel A.; Yan, Peng; Shaikh, Obaid S.; Chung, Raymond T.; Sherman, Kenneth E.; ,
Abstract: Background & Aims: Role of non‐adherence upon virological success with newer oral regimens is unknown. We sought to determine the impact of treatment adherence upon virological outcomes in hepatitis C virus (HCV) infected persons on sofosbuvir (SOF)‐based regimens, using pharmacy prescription data as a measure of adherence. Methods: We analysed HCV infected persons in Electronically Retrieved Cohort of HCV Infected Veterans, who were initiated on SOF‐based regimens, excluding those with human immunodeficiency virus, positive hepatitis‐B surface antigen, hepatocellular carcinoma and missing HCV RNA. Results: The final dataset included following regimens: SOF+simeprevir (SIM) ( n = 1050), SOF+ledipasvir (LDV) ( n = 974), SOF+ribavirin (RBV) ( n = 663, genotype 2 or 3), and SOF+pegylated interferon (PEG)+RBV ( n = 519, genotype 1 or 4). Those treated with a SOF‐based regimen were older and more likely to have cirrhosis, diabetes, chronic kidney disease, higher HCV RNA levels, higher body mass index, compared with 1652 controls receiving a boceprevir‐based (BOC) regimen. Sustained virological response (SVR12) rates for the SOF+SIM and SOF+LDV groups did not decline significantly even when as low as 50% of the full course was prescribed (except SOF+LDV, 90–99% prescriptions had SVR12 of 84.6%; n = 13). SOF+RBV for genotype 2/3 who received 50–80% of the prescriptions, 23/34 (67.6%) achieved SVR12. For persons with genotype 1/4 infection treated with SOF+PEG+RBV, no declines in SVR12 were seen with lower rates of prescriptions (40/43, or 93% SVR12 rate). Conclusions: Sofosbuvir‐based treatment regimens are highly effective in achieving SVR12. This efficacy is not significantly affected when treated persons receive less than a full prescribed course of treatment.